2022
DOI: 10.1029/2022je007301
|View full text |Cite
|
Sign up to set email alerts
|

LRO‐LAMP Survey of Lunar South Pole Cold Traps: Implication for the Presence of Condensed H2O

Abstract: The lunar poles contain regions that experience extreme temperature conditions, enabling them to freeze and trap water (Paige, Siegler, et al., 2010;Watson et al., 1961b). Modeling evidence of water delivery to the lunar surface by various mechanisms, such as comet or meteoroid bombardment, solar wind implantation, and outgassing/eruptions have been postulated (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Although data processing efforts consider scattered sunlight and Earthshine, ensuring that scattered light and Earthshine are not a factor is challenging. Therefore, it is possible that increasing Edge‐band and Off‐band albedos with increasing temperature may arise from far‐UV solar illumination (Byron et al., 2019; Magaña et al., 2022) and/or Earthshine. Lastly, we cannot rule out that this trend may result from unidentified systematic effects, or processes not identified here.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although data processing efforts consider scattered sunlight and Earthshine, ensuring that scattered light and Earthshine are not a factor is challenging. Therefore, it is possible that increasing Edge‐band and Off‐band albedos with increasing temperature may arise from far‐UV solar illumination (Byron et al., 2019; Magaña et al., 2022) and/or Earthshine. Lastly, we cannot rule out that this trend may result from unidentified systematic effects, or processes not identified here.…”
Section: Resultsmentioning
confidence: 99%
“…Non‐PSR regions that experience larger temperature swings (and more intense thermal cycling) would therefore have regolith that is more compact, leading to higher albedos. It has been shown that higher porosity regions experience lower albedos (Gladstone et al., 2012; Magaña et al., 2022; Raut et al., 2018). However, we expect porosity effects to be independent of wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations